Education “Jaman Now”: Reward and Punishment Review - Ismail Darimi; Bachtiar Ismail (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2018)
Many cases that ensnare teachers are related to the punishment of students. Reward and punishment are repressive educational tools. A reward is a motivational tool, a tool that can lead to extrinsic motivation. Rewards can also encourage students to learn better, more actively. Whereas punishment is an unpleasant educational tool, a negative educational tool, but punishment can also be a motivational tool, a tool to encourage student learning. Basically, reward and punishment are two fun educational tools and become drivers of learning for students. But many teachers are trapped inside. The method of reward and punishment influences the improvement of children's motivation in learning